2022
DOI: 10.1002/slct.202200340
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Cu2O/CuO as Active Sites on the Cyclometalated Pd(II)/Cu(II) Nanosheet: Active Centre Formation, Synergistic and Catalytic Mechanism

Abstract: A key to understand relationships between structure and activity is help for rational designing high active catalytic films. In this research, a new bi‐cyclometallic ferrocene imine Pd(II)/Cu(II) catalytic monolayer supported on graphene oxide (GO@Fcl−Pd/Cu) was fabricated, which exhibited a higher activity (TOF=1.48×106 h−1) in Suzuki coupling reaction. Enhanced higher activity was related to the in situ formed Pd/ Cu2O (CuO) active centre on the surface during catalysis. Fe in ferrocene had the redox ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…In the case of the spin-coated film mobilized on the surface of the silicon wafer ( Si/APTES-Fcl-Pd 0.1 Co 0.9 ) (entry 9), a lower yield was obtained due to the irregular orientation of the catalyst molecular in the film, which could improve the effective collision between substrates and active sites to enhance the activity. 57–79 When the catalyst was linked on the surface of the silicon wafer by self-assembly ( Si@APTES-Fcl-Pd 0.1 Co 0.9 ), the catalytic activity was relatively lower than that of GO@APTES-Fcl-Pd 0.1 Co 0.9 (entry 7), reflecting the excellent function of GO. The results above suggested the effects of orientation, preparation method, and a proper ligand and support for the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the spin-coated film mobilized on the surface of the silicon wafer ( Si/APTES-Fcl-Pd 0.1 Co 0.9 ) (entry 9), a lower yield was obtained due to the irregular orientation of the catalyst molecular in the film, which could improve the effective collision between substrates and active sites to enhance the activity. 57–79 When the catalyst was linked on the surface of the silicon wafer by self-assembly ( Si@APTES-Fcl-Pd 0.1 Co 0.9 ), the catalytic activity was relatively lower than that of GO@APTES-Fcl-Pd 0.1 Co 0.9 (entry 7), reflecting the excellent function of GO. The results above suggested the effects of orientation, preparation method, and a proper ligand and support for the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In situ ReactIR has been widely used because of its efficient and convenient detection means to accurately monitor the catalytic process. 64,70,74,78 GO@APTES-Fcl-Pd 0.1 Co 0.9 and (PhCN) 2 PdCl 2 /CoCl 2 ·6H 2 O were used to catalyze the reaction, and the monitored 3D spectrum showed a great difference for the two catalytic processes (Fig. S14a and b, ESI†).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bi-organometallic catalytic monolayer exhibits higher activity than the mono-organometallic catalytic monolayer because of the synergistic effect existing on the catalytic surface, such as the electron distribution of active species. Moreover, active metals or nonactive metals in active sites simultaneously joined in the catalytic process, as described in Scheme 3 [63][64][65][66]. The results indicated that the morphology, catalyst orientation, ligand design, support selection, the rational combination of different metals, and the ratio of multi-metals were crucial factors for achieving a highly active and stable catalyst.…”
Section: Xps Analysis Of Go-tpy-pd1/ni1 During Catalysismentioning
confidence: 99%